A cross-sectional survey on the effects of ambient temperature and humidity on health outcomes in individuals with chronic respiratory disease - Samantha Mekhuri; Shirley Quach; Caroline Barakat; Winnie Sun; Mika L Nonoyama (Canadian Journal of Respiratory Therapy)
# Rationale